How to Master A Seismic Disaster. - Kumagai, J. (IEEE spectrum)
When the next big earthquake hit Tokyo, an early-warning systems could help save lives and properties. Japanese government has spent the last five years constructing an automated earthquake early-warning network. It's the first national system of its kind and by far the most sophisticated. The network is designed to detect the first tremors of an earthquake, calculate the likely source and magnitude, and then broadcast an alert